2018
DOI: 10.1002/bate.201800001
|View full text |Cite
|
Sign up to set email alerts
|

3‐D‐Druck mit Beton: Sachstand, Entwicklungstendenzen, Herausforderungen

Abstract: Die Entwicklung digitaler Betondruckverfahren zur Herstellung von Betonbauteilen direkt auf der Baustelle oder im Fertigteilwerk ist ein entscheidender Schritt auf dem Weg zur Einführung des Industrie‐4.0‐Konzepts in das Bauwesen, nämlich von der bereits existierenden digitalen Bauplanung (CAD, BIM) bis hin zur digitalen Fertigung. Das technologische und wirtschaftliche Potenzial des digitalen Betonbaus wurde inzwischen von vielen am Bau Beteiligten und Forschern erkannt; der Umfang von Innovationsaktivitäten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
0
13
0
5
Order By: Relevance
“…Rheological properties must be fine-tuned since they affect not only the pumping behavior (transport of the material to the printhead) [31,32], extrusion process [33,34], and the shape stability of the deposited filaments, but the quality of the interlayer bond and herewith the properties of final SHCC structure in a hardened state as well [18]. Le et al [2] identified four key characteristics necessary for successful 3D-printing:

Pumpability—The ease and reliability with which material is moved through the delivery system;

Printability—The ease and reliability of depositing material through a deposition device;

Buildability—The resistance of deposited fresh material to deformation under load;

Open time—The period where the above properties are consistent within acceptable tolerances.

…”
Section: Experimental Programmentioning
confidence: 99%
“…Rheological properties must be fine-tuned since they affect not only the pumping behavior (transport of the material to the printhead) [31,32], extrusion process [33,34], and the shape stability of the deposited filaments, but the quality of the interlayer bond and herewith the properties of final SHCC structure in a hardened state as well [18]. Le et al [2] identified four key characteristics necessary for successful 3D-printing:

Pumpability—The ease and reliability with which material is moved through the delivery system;

Printability—The ease and reliability of depositing material through a deposition device;

Buildability—The resistance of deposited fresh material to deformation under load;

Open time—The period where the above properties are consistent within acceptable tolerances.

…”
Section: Experimental Programmentioning
confidence: 99%
“…Das digitale Bauen rückt mehr und mehr in den Blickpunkt von Forschung und Bauindustrie. In den letzten Jahren wurden innerhalb von Pilotprojekten bereits ganze Bauwerke mithilfe des 3D‐Druckverfahrens weitestgehend automatisiert hergestellt . Das Potenzial dieser Verfahrensweise hinsichtlich der ökonomischen Effizienz und der architektonischen Vielfalt ist inzwischen unbestritten.…”
Section: Additive Fertigung Von Bewehrten Elementen – 3d‐druck Mit Caunclassified
“…Hier gelten im Allgemeinen die Ausführungen zur Integration der Bewehrung beim 3D‐Druck mit der „Contour Crafting“‐Methode, welche in Gruppe 1 gehört. Eine eingehendere Darstellung der 3D‐Druckverfahren aus betontechnologischer Sicht wird in geboten.…”
Section: D‐druckverfahren Für Betonbauunclassified